What happens to the mycorrhizal communities of native and exotic seedlings when Pseudotsuga menziesii invades Nothofagaceae forests in Patagonia, Argentina? - Salgado Salomón, María Eugenia; Barroetaveña, Carolina; Pildain, María Belén; Williams Subiza, Emilio Adolfo; Rajchenberg, Mario (Acta Oecologica)
Pseudotsuga menziesii is one of the most widely planted conifers in the Patagonian Andes of Argentina, having invading characteristics that are broadly reported. We studied the mycorrhizal status of seedlings along six Nothofagaceae + P. menziesii invasion matrices to investigate their role in the invasive process, according to these hypothesis: a) The abundance and richness of EM will be higher in seedlings grown in their own soil; b) In the presence of native EM inoculum, the invasive plant will be associated with generalist mycorrhizae (EM and/or AM), c) AM associations will be more abundant in P. menziesii seedlings grown in Interface or native forest soils, d) Mycorrhizal community differences between treatments will alter host fitness (growth and nutritional parameters). Seedlings from Nothofagus dombeyi, N. antarctica, Lophozonia alpina, L. obliqua and Pseudotsuga menziesii were set up in a soil-bioassay that included soils from non-invaded Nothofagaceae forests, pure P. menziesii plantations, and the interface between both. Pseudotsuga menziesii seedlings showed a decreasing, although never null, ectomycorrhizal (EM) colonization pattern from plantations to non-invaded forests, mainly with exotic EM species. Hebeloma mesophaeum and Wilcoxina sp. 1, two EM species with cosmopolitan distribution, were found to be shared by both tree species. Hebeloma hiemale and Wilcoxina sp. 1, common mycorrhizal partners of P. menziesii in Patagonia although not registered from Nothofagaceae forest, were found to be associated with N. antarctica, being the first report for both fungal species. Pseudotsuga menziesii seedlings showed the ability to form different arbuscular mycorrhiza (AM) colonization types (Paris-, Arum-, Both- and Intermediate-types) depending on the treatments, with significantly higher presence of Intermediate-type in the Interface treatment, where colonization was low. The shared EM species and the presence of different AM colonization types imply enhanced possibilities for invasive P. menziesii ...